(3GdWHbGJ GdcHQis - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s ((3eMeO Hf Hf MSf Hf Ydi GdgQbdi s)
(3ChdgG (B:s
(3PcQ ef CJe Edjg QShd Gddg Udi Gddg Ydjg hSde CNHQfG eMeO Hf eUYH GdbQbSGfi bGd QShd Gddg Udi Gddg Ydjg hSde CfG SjO hdO BOe s
(3BNQgG (B:s
(3fRd Ydjg EfG aJMfG dc aJMkG eHjfkG abGd LHQjd Jgfjc jGQShd Gddg hgfGg GdeSdehf Je GdcJGH s
(3cJH GdcJGH Hbde Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs